Traumatic injuries among adult obese patients in southern Taiwan: a cross-sectional study based on a trauma registry system - Jung-Fang Chuang; Cheng-Shyuan Rau; Pao-Jen Kuo; Yi-Chun Chen; Shiun-Yuan Hsu; Hsiao-Yun Hsieh; Ching-Hua Hsieh (BMC, 2016)
Abstract Background The adverse impact of obesity has been extensively studied in the general population; however, the added risk of obesity on trauma-related mortality remains controversial. This study investigated and compared mortality as well injury patterns and length of stay (LOS) in obese and normal-weight patients hospitalized for trauma in the hospital and intensive care unit (ICU) of a Level I trauma center in southern Taiwan. Methods Detailed data of 880 obese adult patients with body mass index (BMI) ≥ 30 kg/m2 and 5391 normal-weight adult patients (25 > BMI ≥ 18.5 kg/m2) who had sustained a trauma injury between January 1, 2009 and December 31, 2013were retrieved from the Trauma Registry System. Pearson's chi-squared, Fisher's exact, and independent Student's t-tests were used to compare differences between groups. Propensity score matching with logistic regression was used to evaluate the effect of obesity on mortality. Results In this study, obese patients were more often men, motorcycle riders and pedestrians, and had a lower proportion of alcohol intoxication compared to normal-weight patients. Analysis of Abbreviated Injury Scale scores revealed that obese trauma patients presented with a higher rate of injury to the thorax, but a lower rate of facial injuries than normal-weight patients. No significant differences were found between obese and normal-weight patients regarding Injury Severity Score (ISS), Trauma-Injury Severity Score (TRISS), mortality, the proportion of patients admitted to the ICU, or LOS in ICU. After propensity score matching, logistic regression of 66 well-matched pairs did not show a significant influence of obesity on mortality (odds ratio: 1.51, 95 % confidence interval: 0.54-4.23 p = 0.438). However, significantly longer hospital LOS (10.6 vs. 9.5 days, respectively, p = 0.044) was observed in obese patients than in normal-weight patients, particularly obese patients with pelvic, tibial, or fibular fractures. Conclusion Compared to normal-weight patients, obese patients presented with different injury characteristics and bodily injury patterns but no difference in mortality.